Extract and estimate the peroxidase enzyme from bean kales Phaseolus vulgaris L - Mra Al-Kateb; Abdullah Al-Nuaimi (College of Education for Pure Sciences, 2007)
Peroxidase enzyme was extracted from callus of different explants and immature embryos of Phaseolus vulgaris L. .The maximum activity of enzyme showed in the embryos callus sample.The higher activity of enzyme was in the ( 4months) age of callus for each of leaves ,roots and embryos and in (6months) for cotyledons callus,the stems callus recorded best activity in (2months)old.Using of ammonium sulphate precipitation result in high enzyme activity in all samples.When the exchange chromatochraphy was used to purifiy stems callus extract,(5)protein apexes observed and ( 4 )of it was active .In the separation of proteins by using the electrofousing techniques, the samples of embryos ,leaves,stems,cotyledons and roots were separated at pH range (5.13- 6.14 ).The minimum activity of enzyme observed at ( 4day) age for all explants samples,but the maximum activity was in the roots samples at (14day)age